2004
DOI: 10.1152/ajpcell.00393.2003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the β-subunit for nongastric H-K-ATPase in rat anterior prostate

Abstract: The structural organization of nongastric H-K-ATPase, unlike that of closely related Na-K-ATPase and gastric H-K-ATPase, is not well characterized. Recently, we demonstrated that nongastric H-K-ATPase α-subunit (αng) is expressed in apical membranes of rodent prostate. Its highest level, as well as relative abundance, with respect to α1-isoform of Na-K-ATPase, was observed in anterior lobe. Here, we aimed to determine the subunit composition of nongastric H-K-ATPase through the detailed analysis of the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…No specific b-subunit that assembles with the nongastric H,K-ATPase has been found. Recent studies suggest that the Na,K-ATPase b 1 -subunit is probably the partner for the non-gastric H,K-ATPase isoform in vivo [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No specific b-subunit that assembles with the nongastric H,K-ATPase has been found. Recent studies suggest that the Na,K-ATPase b 1 -subunit is probably the partner for the non-gastric H,K-ATPase isoform in vivo [11].…”
Section: Introductionmentioning
confidence: 99%
“…The gastric H,K-ATPase is located in intracellular tubulovesicular elements in the resting parietal cell and relocates to the secretory canalicular (apical) membrane upon stimulation of acid secretion [17]. The non-gastric H,K-ATPase is found on the apical membranes of epithelial cells in the colon, kidney, and prostate gland [11,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Also, nongastric H-K-ATPase does not have a specific ␤-subunit but employs the ␤ 1 isoform of Na-K-ATPase (8,31,42). This fact is relevant to the mechanisms of cellular sorting of X-K-ATPases because H-KATPase and Na-K-ATPase are localized to different membranes in polarized epithelial cells.…”
mentioning
confidence: 99%
“…This differential localization and sorting depends on the interaction of ATP12A with the beta-subunit of the Na + /K + ATPase [32]. Recently it has been shown that in the rat anterior prostate the Na + /K + ATPase beta1-subunit functions also as the authentic beta-subunit of the non-gastric H + /K + ATPase and putatively accounts for the intracellular sorting of the X-K-ATPase isoforms [33]. Interestingly, the Na + /K + ATPase beta1-subunit was found to be down-regulated by androgens in human LNCaP-FGC prostate cancer cells and human prostate cancer xenografts [34].…”
Section: Discussionmentioning
confidence: 99%